2010
DOI: 10.1510/icvts.2009.229542
|View full text |Cite
|
Sign up to set email alerts
|

Impaired anti-platelet effect of aspirin, inflammation and platelet turnover in cardiac surgery☆☆☆

Abstract: A reduced platelet inhibitory response to acetyl salicylic acid (ASA) has been associated with an increased risk of graft thrombotic occlusion after coronary artery bypass grafting (CABG). We performed a prospective, observational study of 18 patients on 100 mg/day ASA before and after CABG. We assessed antiplatelet response to ASA and its relationship with platelet turnover, inflammatory markers, and soluble thrombomodulin (sTM) levels. All patients showed optimal response to ASA preoperatively but had higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
1
19
0
4
Order By: Relevance
“…Arazi et al identified a significant correlation between this condition and a postoperative ASA nonresponse. 16 Assuming that a longer extracorporeal circulation leads to greater impairment of platelet function, one could suppose that the identification of the CPB time as an independent risk factor for an ASA nonresponse in the present study reflects a higher platelet turnover in patients with a longer CPB time. Because no laboratory markers for an increased platelet turnover were measured in this study, this question cannot be answered by the current results.…”
Section: Discussionmentioning
confidence: 68%
“…Arazi et al identified a significant correlation between this condition and a postoperative ASA nonresponse. 16 Assuming that a longer extracorporeal circulation leads to greater impairment of platelet function, one could suppose that the identification of the CPB time as an independent risk factor for an ASA nonresponse in the present study reflects a higher platelet turnover in patients with a longer CPB time. Because no laboratory markers for an increased platelet turnover were measured in this study, this question cannot be answered by the current results.…”
Section: Discussionmentioning
confidence: 68%
“…When collagen was used as agonist, inhibition was lower, whereas when arachidonic acid and thrombin receptor activator peptide were used, tomato showed no inhibitory effect [24]. These results rule out the platelet antiaggregant activity of salicylic acid or a related species [25].…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with this notion, elevated plasma TM levels have been found to correlate with atherosclerosis (119,158), cardioembolic stroke (38), obesity (165), Lupus erythomatosus-associated metabolic syndrome (105), preeclampsia (130), sepsis-associated disseminated intravascular coagulation (DIC) (90), and severe acute respiratory syndrome (SARS) (91). Significantly elevated plasma TM levels have also been observed in patients following coronary artery bypass graft (CABG) surgery (10,78). By contrast, several clinical studies report on vascular pathologies manifesting reduced sTM levels.…”
Section: Posttranslational Regulationmentioning
confidence: 99%